Rate effects on localized shear deformation during nanosectioning of an amorphous thermoplastic polymer. (15th December 2017) - Sun, Fengzhen; Li, Hu; Leifer, Klaus; Gamstedt, E. Kristofer
Highlights: Nanosectioning of polymers is performed using an instrumented ultramicrotome. Shear localization structures form on the sectioned surface of the polymer at or above a critical sectioning speed. An adiabatic shearing model and a suitable constitutive law are used to model the thermomechanical behavior of the polymer during sectioning. An onset speed for shear localizations is predicted, agreeing with the experimental results. Abstract: To investigate the effects of loading rate on the thermomechanical behavior of thermoplastic polymer during sectioning, polymethyl methacrylate (PMMA) sections with a thickness below 100 nm were made at different sectioning speeds by an instrumented ultramicrotome and the sectioning forces were measured. Atomic force microscopy was used to characterize the topographical features of the sectioned surfaces. Periodic structures of shear localizations were observed to form when the sectioning speed exceeded a critical value. With the measured sectioning parameters and other parameters determined based on previous studies, the effects of sectioning speed on the thermomechanical response of this polymer were analyzed using an existing adiabatic shearing model and a suitable constitutive law. A sectioning speed for the onset of shear localization was predicted, agreeing with the experimental results. The method presented in this work provides an approach to analyze the formation of shear localizations in polymers at the nanometer scale deformation.